Physiological alterations during a basketball season in college women - Kleinschmidt, L. A.; Butts, N. K.; Kennedy, C.; Meyer, J.; Mowbray, R. (Medicine & Science in Sports & Exercise, 1997)
An NCAA Division III women's basketball team (N = 13) was measured immediately prior to the commencement and upon completion of a competitive season. Neither aerobic nor anaerobic variables changed over the season. Maximum heart rates in scrimmages and games were significantly higher than in any testing session or protocol. Implication: Physiological test results are not changed by a season of competitive basketball in college women. The nature of physiological tests, as demonstrated by heart rates, is very different to the circulatory demands of scrimmages and games. Consequently, physiological tests may not be indicative of the "fitness" required for participating in collegiate basketball.